Keragaman dan Kelimpahan Populasi Liriomyza spp. (Diptera: Agromyzidae) dan Parasitoidnya pada Tanaman Solanaceae di Provinsi Bali - Wijaya, I Putu Arya; Wijaya, I Nyoman; Darmiati, Ni Nengah (Nandur; Vol 2 No 3 (2022), 2022)
Leaf miner or Liriomyza spp. is one of the pests that attack Solanaceae plants in Bali by damaging the leaves of the plant. This study entitled Population Diversity and Abundance of Liriomyza spp. (Diptera: Agromyzidae) and its Parasitoids in Solanaceae Plants in Bali Province. Aims to determine the community structure of Liriomyza spp. and the degree of parasitization associated with Liriomyza spp. This research was conducted in all District/City in the Province of Bali where there are Solanaceae plants. Research using purposive method in planting samples taken as many as 5 (points) in each District/City in Bali, at an altitude of 0-1400 masl. Sampling was done by taking the leaves of plants that showed early symptoms of Liriomyza spp. The results showed that there were 5 (five) species of Liriomyza spp. found in the field, namely Liriomyza brassicae, Liriomyza sativa, Liriomyza huidobrensis, Liriomyza trifolii and Liriomyza chinensis and found 7 (seven) species of parasitoids namely Opius chromatomyaie., Hemiptarsenus varicornis, Neochrysocharis okazakii, N. formosa, Opius dissitus, Pnigalio sp , and Clostrocerus sp.  the community structure and parasitoid parasitization level have index values. abundance, diversity and dominance that vary on the plant Solanaceae in each District/City in Bali.